(3aJM GdhgGH HTQM GdBOGHs - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s; (3GdSeQbfOj , TeS GdOjf eMeO Hf GTQa GdMSjfj GdSeQbfOj,J (B690 (3g` s ((3fGUQ CUdGf s)
(3ChdgG (B:s
(3GdMeO ddg GdhGgH GdefGf hHYO agPG TQM GdcJGH GdSeQbfOi jMd CdaGXg hSejJg s
(3BNQgG (B:s
(3hEfeG bdfG Ef CMO GdEecGfjf KGHJ , dC, Tehd GdEecGfjf ddhbJjf , EeG C, jchf YdI GdCMO GdTehdjf eWdbkG , ChdkG hYdi GdJbOjQjf jdRe CMO GdEecGfjf Je TQM GdQSGdI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJH GdeJf HGdMeQI s
(3YdjgG NJe GdeOQSI GdC;eOjI HMdH s
(3ef GdcJH GdJi hbagG CMeO CafOi WQRGOg Ydi GdeOQSI s
Keywords: (3GdadSaI hGdefWbs